2013
DOI: 10.1515/rjti-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Application of GPR and FWD in Assessing Pavement Bearing Capacity

Abstract: The process of pavement maintenance and rehabilitation starts by collecting the data which will form the base for evaluation of pavement functional and structural condition. Collection of data can be performed by destructive and non-destructive testing. Usually preferred are the non-destructive methods, that do not damage the pavement, and the process of pavement evaluation is objective and repeatable. Non-destructive testing methods are becoming more and more popular, especially for assessing the structural c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…This process also enabled calculation of the quantity of each material removed and overlaid and also, when available, calculation of the cost of these materials. Another application is aimed at modelling structural characteristics of the pavement measured through load tests with a Falling Weight Deflectometer [2], [10]. Two parameters were modelled; the central deflection D1 (Figure 10) that reflects general structural condition of the pavement, and the farther deflection D7, located at 1.8 m from the centre of the load plate, which reflects the stiffness of the subgrade.…”
Section: Figure 9 Modelling Various Phases Of Test Section Rehabilitmentioning
confidence: 99%
“…This process also enabled calculation of the quantity of each material removed and overlaid and also, when available, calculation of the cost of these materials. Another application is aimed at modelling structural characteristics of the pavement measured through load tests with a Falling Weight Deflectometer [2], [10]. Two parameters were modelled; the central deflection D1 (Figure 10) that reflects general structural condition of the pavement, and the farther deflection D7, located at 1.8 m from the centre of the load plate, which reflects the stiffness of the subgrade.…”
Section: Figure 9 Modelling Various Phases Of Test Section Rehabilitmentioning
confidence: 99%
“…Sybilski et al (2012) present a case study of premature cracking where combination of GPR with FWD methods and laboratory measurements allowed the identification of severe water content as the reason for cracking. Domitrović and Rukavina (2013) deal with the comparison of pavement layer moduli calculated from FWD deflection data using layer thickness obtained by GPR and coring. Furthermore, this paper concluded that there is a tendency in reinforcement projects to apply recycling methods and use recycled materials so, knowing the continuous thickness of asphalt layers by GPR is essential in order to determine the optimum thickness available for milling and thus achieve optimization of recycling process.…”
Section: Roads and Pavementsmentioning
confidence: 99%
“…FWD is considered the most effective NDT device for pavement deflection measurements worldwide [1][2][3]. It simulates the pavement responses under traffic loading [4] by applying an impulse load and measuring the pavement deflection bowl (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%